Challenges Faced by the School in Adapting the Implementation of Kurikulum Merdeka: A Case Study of Indonesia’s Border Area - Fathurrozi, Muhammad; Maliqul Hafis; Sahrawi (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to identify the challenges faced by teachers and schools while implementing Kurikulum Merdeka, as well as the strategy and support needed by teachers and schools in implementing Kurikulum Merdeka in the border area of Indonesia. This research used a case study approach. Data were collected through interviews and a questionnaire. Thematic analysis and statistical descriptive methods were employed to analyze the data. The research took place in Temajuk village, Paloh sub-district, Sambas regency, specifically at SMP N 4 Paloh and SMA N 2 Paloh. The subject included both school principals and five selected teachers from each school. This research was conducted on March 14, 2025. The principals were interviewed, followed by a questionnaire distribution to the selected teachers. The data collected were analyzed using thematic analysis and statistic descriptive technique. The research results show that SMA N 2 Paloh still faces the limitation of supporting facilities and the teachers' understanding due to a lack of special training. The schools have shown efforts to achieve maximum implementation through the optimization platform PMM and the teachers' study group. While SMP N 4 Paloh is still faced with the limitation of teachers' understanding, an inadequacy of training, and the limitation of supporting infrastructure. The infrastructure improvement and an in-depth training will certainly help the effectiveness of the Implementation of Kurikulum Merdeka in the border area.